Managerial Approach toward Enhancing Agriculture Management: Based on New Technology Methods - Ghanem, Yasmeen (جامعة النجاح الوطنية, 2021)
Despite the availability of many modern methods that rely on smart technologies to monitor farmers’ fields with adequate and real data, Palestinian farmers continue to use traditional methods of field management based on past experience and information. To help farmers understand the need to use modern systems, we determine the problems they face then evaluate their intentions to adopt smart systems and influencing factors. To collect data, a survey on 91 olive farmers in Jenin district of Palestine was conducted. The data was tested and analyzed using the SPSS. Olive farmers in Jenin revealed that the two major challenges they face are the weather change and the pest control, and therefore, they intend to adopt smart management systems. The developed smart system combines irrigation, fertilization and pest control. The system helps in: reduces resources, identifies the disease in the early stages, and reduces the risk of disease spreading in the field. To achieve this smart approach the collaboration among many institutions is needed. Implementing such practices will strengthen farmers in their new journey which will lead to a new agricultural revolution in developing countries such as Palestine.
نهج إداري لتعزيز الإدارة الزراعية: بالاعتماد على وسائل تكنلوجية حديثة